2023
DOI: 10.1038/s41467-023-37867-1
|View full text |Cite
|
Sign up to set email alerts
|

The fragmentation-induced fluidisation of pyroclastic density currents

Abstract: Pyroclastic density currents (PDCs) are the most lethal volcanic process on Earth. Forecasting their inundation area is essential to mitigate their risk, but existing models are limited by our poor understanding of their dynamics. Here, we explore the role of evolving grain-size distribution in controlling the runout of the most common PDCs, known as block-and-ash flows (BAFs). Through a combination of theory, analysis of deposits and experiments of natural mixtures, we show that rapid changes of the grain-siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…This general effect is compounded by processes like PDC channelization and overbanking, which also depend on flow size and mobility, and topography surrounding the vent location. All this is compatible with previous observations made at several volcanoes worldwide (e.g., Aravena & Roche, 2022; Breard et al., 2023; Charbonnier et al., 2020; Charbonnier & Gertisser, 2012; Gueugneau et al., 2020; Ogburn & Calder, 2017; Ogburn et al., 2014; Tennant et al., 2021; Tierz et al., 2018). Notwithstanding, it is also important to place the PDC modeling developed using TITAN2D into the wider context of what is currently known in terms of PDC dynamics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This general effect is compounded by processes like PDC channelization and overbanking, which also depend on flow size and mobility, and topography surrounding the vent location. All this is compatible with previous observations made at several volcanoes worldwide (e.g., Aravena & Roche, 2022; Breard et al., 2023; Charbonnier et al., 2020; Charbonnier & Gertisser, 2012; Gueugneau et al., 2020; Ogburn & Calder, 2017; Ogburn et al., 2014; Tennant et al., 2021; Tierz et al., 2018). Notwithstanding, it is also important to place the PDC modeling developed using TITAN2D into the wider context of what is currently known in terms of PDC dynamics.…”
Section: Discussionsupporting
confidence: 92%
“…Pile sources, on the contrary, given their pseudo‐instantaneous release of material, would create flows that transition into an “inertial regime,” meaning flows that are minimally influenced by (forcing) conditions at the source (cf. Breard et al., 2023; Doronzo, 2012), more rapidly, and over shorter distances, for a given combination of flow size and mobility. Investigating such flow transitions following a systematic, ideally multi‐model, approach (e.g., Gueugneau et al., 2021; Ogburn & Calder, 2017; Patra et al., 2020), and using probabilities of PDC inundation to fully capture uncertainty, could be a fruitful topic for future research, facilitated by the use of zGP emulators (Spiller et al., 2023).…”
Section: Discussionmentioning
confidence: 98%
“…Since debris flows are also thought to be strongly controlled by granular segregation ( 62 ), accounting for shape in debris flow modeling could be doubly important. Another recent study found that the temporal evolution of angular grains in a pyroclastic flow determines flow rheology ( 63 ). Indeed, changes in packing fraction known to affect rheology have also been shown to result in qualitative shifts in segregation trends ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deposits associated with both dense and dilute PDCs generally show a decay in median grain size with distance from source, particularly for dilute PDCs (Figure 1). This relative increase in fines with distance is related to two main mechanisms: 1) fragmentation and attrition of particles, and 2) preferential deposition of coarse particles that cannot be suspended by turbulent eddies in dilute PDCs (Valentine, 1987;Dufek and Manga, 2008;Manga et al, 2011;Kueppers et al, 2012;Brosch et al, 2022;Breard et al, 2023).…”
Section: Grain Sizementioning
confidence: 99%
“…Entrainment of cooler ambient air at the free surface acts to further stratify the current by modifying the thermal profile and by reducing PDC density, diluting the overriding ash cloud (Benage et al, 2016;Sher and Woods, 2017). With increasing distances from source, the mean particle size is reduced, and particles commonly become rounder due to particle-particle collisions leading to abrasion that progressively removes small chips and asperities on pyroclast exteriors (Dufek and Manga, 2008;Kueppers et al, 2012;Jones et al, 2016;Hornby et al, 2020;Breard et al, 2023). The successful segregation and removal of fine particles from PDCs can create co-PDC ash plumes, dominated by particles with diameters <90 µm (Engwell and Eychenne, 2016).…”
Section: Introductionmentioning
confidence: 99%